Correcting market failure? Stalled regeneration and the state subsidy gap. Issue 1 (2nd January 2022) - Gray, Neil
Abstract : This paper develops the neologism state subsidy gap to underscore the necessity of state intervention in the formation and potential closure of rent gaps. The state subsidy gap is the economic gap that must be bridged by the state to make a currently unviable urban investment scenario potentially profitable for private developers. The pertinence of this conception is particularly apparent in old industrial, relatively impoverished cities where global capital is less likely to dump its surpluses with secure expectation of profitable returns. The issue is exacerbated in economically risky neighbourhoods encompassing fragmented land ownership, poor infrastructure and large-scale areas of urban devalorisation. Such conditions necessitate substantial derisking public intervention if 'market failure' is to be addressed—yet success is never guaranteed and is far from universal. It is argued that much closer attention to the stalling, interruption or failure of urban regeneration projects is imperative given the extent of public expenditure and the limited social outcomes arising from attempts to correct market failure. Here, the concept of the state subsidy gap shows its value, shedding light on unjust social outcomes, exposing capitalism's inherent vulnerabilities, and illustrating the dependence of private capital on public interventions for its reproduction.